PENGGUNAAN KONJUNGSI KOORDINATIF DALAM BERITA EDITORIAL SURAT KABAR TRIBUN JAMBI BULAN JANUARI 2019 - Firman Tara; Nur Adawiya WM (Universitas Batanghari, 2020)
The purpose of this research is to describe the use of coordinating conjunction on editorial news of Tribun Jambi January 2019. This research uses qualitative descriptive method. The data is in the form of sentence which contains coordinating conjunction. The source of the data is the news text on editorial news column of Tribun Jambi newspaper January 2019. The result of the research shows that there are 5 types of conjunctions used. First, there are expressions of coordinating conjunction of addition. Second, there are 3 expressions of coordinating conjunction of sequence. Third, there are 12 expressions of coordinating conjunction of contrast. Forth, there are 11 expressions of coordinating conjunction of choice. Fifth, there are 2 expressions of coordinating conjunction of explanation. Meanwhile there are two types of conjunction which are not found in the newspaper column; affirmation and compound conjunction.